2016
DOI: 10.1007/s12565-016-0342-1
|View full text |Cite
|
Sign up to set email alerts
|

An anatomical study of wormian bones from the eastern part of India: is genetic influence a primary determinant of their morphogenesis?

Abstract: Over the years a number of investigators have analysed the morphology of wormian bones in different population groups across the world. There have been significant variations between findings reported in these studies, and this has prompted researchers to focus on the influence of genetic factors on the morphology of these bones. In the light of the above observation, we considered it justified to conduct anatomical studies on wormian bones in different population groups; hence, we undertook the present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
3
16
0
Order By: Relevance
“…In our study, conducted on Greek skulls, the incidence of WBs presence (74.7%) is remarkably high. A similar high incidence (80.32%) was reported in Chinese [5], whereas in West Anatolian and Eastern Indian skulls, the reported incidences were 59.3% and 45%, respectively [8,14]. The lowest incidence (9%) was reported by Govsa et al [15] in Turkish skulls.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In our study, conducted on Greek skulls, the incidence of WBs presence (74.7%) is remarkably high. A similar high incidence (80.32%) was reported in Chinese [5], whereas in West Anatolian and Eastern Indian skulls, the reported incidences were 59.3% and 45%, respectively [8,14]. The lowest incidence (9%) was reported by Govsa et al [15] in Turkish skulls.…”
Section: Discussionsupporting
confidence: 61%
“…13-15).The number of WBs in each suture demonstrated a wide range. LS and CS presented the higher number of WBs(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)…”
mentioning
confidence: 99%
“…In the current study, we also noticed a high incidence (23.57%) of wormian bones at the lambda; which is also known as Os Incae or Inca bone, with a highly variable incidence in other populations like; 21.21% in East Indian population [31], 46% in North Karnataka region [29], 1.32% in Central India [32] and 14% in South Indian population [20]. The reason for the presence of wormian bones at Lambda may be that the interparietal part of the squamous occipital bone and the highest nuchal lines develops in membrane, usually from two pairs of ossification centres [33].…”
Section: Resultssupporting
confidence: 71%
“…), the number of bones in the cranium can vary due to occasional appearance of wormian (intra‐sutural) bones (Hess, ; Ghosh et al. ), and there are many more examples of unpredictable anatomy in anatomical and surgical literature. Some of these differences may be specified genetically, but studies of monozygotic twins have demonstrated that histogenesis can vary even when driven by exactly the same ‘genetic programme’.…”
Section: Introduction: the Paradox Of Anatomical Variationmentioning
confidence: 99%
“…One of the first things that medical students learn of human anatomy, usually to their frustration, is that its details are surprisingly variable. Blood vessels can vary in route and number (D aescu et al 2012;Bertrand et al 2014;Silva et al 2014;Marco-Clement et al 2016;Tomaszewski et al 2017), innervation of the same structure can differ between individuals (Matejc ık, 2010; Henry et al 2016;Wolf et al 2016), the number of bones in the cranium can vary due to occasional appearance of wormian (intrasutural) bones (Hess, 1946;Ghosh et al 2017), and there are many more examples of unpredictable anatomy in anatomical and surgical literature. Some of these differences may be specified genetically, but studies of monozygotic twins have demonstrated that histogenesis can vary even when driven by exactly the same 'genetic programme'.…”
mentioning
confidence: 99%